Pengaruh Persepsi Kemudahan Terhadap Keputusan Pembelian Di Online Shop Tokopedia Dengan Kepuasan Sebagai Variabel Intervening - Ahmad Rafik; Nyoman Suardhita (Prisani Cendekia, 2023)
The purpose of this study was to analyze the effect of perceived convenience on satisfaction, to analyze the effect of perceived convenience on purchasing decisions, to analyze the effect of satisfaction on purchasing decisions and to analyze the effect of perceived ease of purchase on purchasing decisions through satisfaction at Tokopedia's Onlie Shope. The research approach used in this study is the associative method. The analysis technique uses Partial Least Square (PLS). As for the results of the study, it shows that there is an effect of perceived convenience on purchasing decisions at the Online Shope Tokopedia. There is an influence of Perceived Convenience on Purchasing Decisions at Online Shope Tokopedia. There is an influence of Perceived Convenience on Purchasing Decisions with Satisfaction as an intervening variable at Tokopedia Online Shope